Exploring Psychological Needs and Burden of Care in Parents of Children with Hemato-Oncological Diseases - Loredana Benedetto; Irene Marino; Francesca Ronco; Grazia Iaria; Luisa Foletti; Massimo Ingrassia (Hemato, 2022)
Caring for a child with an acute/life threatening disease exposes parents to multiple stressors and challenges, resulting in a physical and psychological burden. Parents experience many health-related issues and worries that often remain underestimated. The aims of the study were: (a) to explore the associations between needs/disease-related issues and burden in parents of children with leukemia or Hodgkin’s disease; (b) to estimate predictors of parents’ burden using a stepwise linear regression analysis. Children (N = 33) followed an active therapy protocol (48.5%), or they were off therapy (51.5%). Forty-four parents completed surveys on caregiver burden levels and needs to cope with the child’s illness. Parental factors impacting burden (personal resources, loss of control, depression) and child’s quality of life (QoL) were also assessed. Among the needs, information about the illness/resources were the most urgently expressed by parents, followed by reassurance against fears for the child’s development and future well-being. Parents reported severe (27.3%) and moderate (22.7%) burden, with a higher percentage of caregivers with severe burden in the off-therapy phase (18.2%) than in the active-therapy phase (9.1%). The child’s decreased physical QoL and parent’s loss of control predicted higher levels of burden. The implications for supportive interventions aimed at responding to parental needs and preventing caregiver burden are discussed.